Synonymic notes on some species of Chironomidae (Diptera) described by Dr. M. Sasa - Kobayashi, Tadashi; Endo, Kazuo (Zootaxa, 2008)
Holotypes of 36 species in the Sasa collection at the National Science Museum, Tokyo, have been reexamined. Among these 16 species belong in Tanypodinae, 5 species in Diamesinae, 5 species in Prodiamesinae, and 10 species in Chironominae. Consequently, 32 new synonyms and 3 new combinations are established, and one species is reconfirmed. Tanypodinae: Yaequintus irioquereus Sasa et Suzuki, 2000 is transferred to the genus Denopelopia and D. bractea Cheng et Wang, 2005 is a new junior synonym of D. irioquerea; this is the first record of the genus Denopelopia from Japan. Krenopelopia kurobefasciata Sasa et Okazawa, 1992 and Zavrelimyia inawaquerea Sasa, Kitami et Suzuki, 2000 are new junior synonyms of Natarsia tokunagai (Fittkau, 1962). Krenopelopia amaminova Sasa, 1990, K. togavicea Sasa et Okazawa, 1992, K. yunouresia Sasa, 1989, Monopelopia okigenga Sasa, 1990, Paramerina kurobekogata Sasa et Okazawa, 1992, and P. tokararesea Sasa et Suzuki, 1995 are new junior synonyms of Paramerina divisa (Walker, 1856). Paramerina okimaculata Sasa, 1990 is reconfirmed. Krenopelopia togatibea Sasa et Okazawa, 1992 is a new junior synonym of Psectrotanypus orientalis Fittkau, 1962. Krenopelopia joganflava Sasa et Okazawa, 1991 is a new synonym of Rheopelopia ornata (Meigen, 1838). Zavrelimyia inaveua Sasa, Kitami et Suzuki, 2001 is a new junior synonym of Tanypus punctipennis Meigen, 1818. Trissopelopia oyabetrispinosa Sasa, Kawai et Ueno, 1988 is a new junior synonym of T. longimana (Staeger, 1839). Paramerina tusimuheia Sasa et Suzuki, 1999 is transferred to the genus Zavrelimyia. Diamesinae: Boreoheptagyia kurobeia Sasa et Okazawa, 1992 is a new junior synonym of B. brevitarsis (Tokunaga, 1936). Diamesa kurobedistalis Sasa et Okazawa, 1992 is a new junior synonym of D. alpina Tokunaga, 1936. Pseudodiamesa sunabacedea Tanaka et Sasa, 2001 is transferred to the genus Diamesa. Potthastia togabicolis Sasa et Okazawa, 1992b is a new junior synonym of P. gaedii (Meigen, 1838). Sympotthastia toyamayezea Sasa, 1996 is a new junior synonym of S. takatensis (Tokunaga, 1936). Prodiamesinae: Prodiamesa chuzenigra Sasa, 1989 and Prodiamesa kamidefea Sasa et Hirabayashi, 1993 are new junior synonyms of Monodiamesa bathyphila (Kieffer, 1918). Prodiamesa nagaii Sasa et Kawai, 1985, P. otukii Sasa et Tanaka, 2000 and P. toneheia Sasa et Tanaka, 2000 are new junior synonyms of P. levanidovae Makarchenko, 1982. Chironominae: Chironomus daitoabeus Sasa et Suzuki, 2001, Daitoyusurika daitofegea Sasa et Suzuki, 2001, and Yaesecundus iriobeceus Sasa et Suzuki, 2000 are new junior synonyms of Chironomus crassiforceps (Kieffer, 1916). Cryptotendipes sibaabeus Sasa, Sumita et Suzuki, 1999 is a new junior synonym of Cladopelma edwardsi (Kruseman, 1933). Harnischia sibabecea Sasa, Sumita et Suzuki, 1999 is a new junior synonym of H. ohmuraensis Kobayashi et Suzuki, 1999. Prochironomus irioheius Sasa et Suzuki, 2000 is a new junior synonym of Paratendipes nigrofasciatus Kieffer, 1916. Chironomus daitobeceus Sasa et Suzuki, 2001 and Polypedilum daitoneoum Sasa et Suzuki, 2002 are new junior synonyms of Polypedilum (Polypedilum) nubifer (Skuse, 1889). P. (P.) chubetuabeum Sasa et Suzuki, 2001 is a new junior synonym of P. (P.) tsukubaense (Sasa, 1979). Tanytarsus ginzanquartus Sasa et Suzuki, 1998 is a new junior synonym of Rheotanytarsus rivulophilus Kawai et Sasa, 1985.